HUBUNGAN KONSUMSI BUAH SAYUR DAN MAKANAN BERLEMAK DENGAN OBESITAS PADA IBU RUMAH TANGGA DI AMONGROGO RW 3 LIMPUNG BATANG - Riris Eryani; Enik Sulistyowati; Sunarto Sunarto; Kun Aristiati Susiloretni (Poltekkes Kemenkes Semarang, 2015)
Background : The prevalence of obesity for adult women in Indonesia according to the National Riskesdas in 2013 reached 14.8%. Obesity prevalence in Indonesia has increased from year to year. Factors that cause obesity include consumption patterns, lack of physical activity, genetic problems, psychological factors, and social factors.Objective : to determine the relationship between consumption of vegetable fruits and fatty foods with obesity in housewives in Amongrogo Village, Limpung Batang District.Method : This type of research includes community nutrition with cross sectional approaches. The number of research samples is 65 samples of housewives. Data collected were BB, TB, fruit consumption, vegetable consumption, and consumption of fatty foods with the interview method using the Semi-Quantitative Food Frequency questionnaire. To find out the relationship between variables used Chi-Square test and Fisher Exact test with 95% confidence level.Results : the results of the study showed that obesity prevalence in Amongrogo Village was 46.2%. Fruit consumption per day is less than 2 portions, 61.5%. Vegetable consumption per day is less than 3 servings of 70.8%. Consumption of fruits and vegetables is less than 400 grams per day 67.7%. Consumption of fatty foods more than 6 servings per day 83.1%.Conclusion : the results of statistical analysis showed that there was no relationship between fruit consumption and obesity (p = 0.194), there was no correlation between consumption of vegetables and obesity (p = 0.900), there was no relationship between consumption of fruits and vegetables with obesity (p = 0.368) , there is a relationship between consumption of fatty foods with obesity (p = 0.004, RP = 6.56). It is recommended to hold counseling related to obesity and holding joint gymnastics or sports activities.